2013
DOI: 10.1115/1.4024991
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Pedestrian-Bridge Dynamic Interaction

Abstract: The pedestrian-bridge dynamic interaction problem in the vertical direction based on a bipedal walking model and damped compliant legs is presented in this work. The classical finite element method, combined with a moving finite element, represents the motion of the pedestrian in the dynamic analysis of a footbridge. A control force is provided by the pedestrian to compensate for the energy loss due to the system damping in walking and to regulate the walking performance of the pedestrian. The effects of leg s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…The behaviour of IPMs is harder to analyse and, therefore, less practical for day-to-day design practice. While a linear SDOF MSD model needs only three parameters ( , , and ) to be defined, similar IPMs need a minimum of six independent parameters such as body mass, angle of attack, length of leg at rest, leg stiffness, leg damping ratio, and initial system energy and, in the case of more complex models, feet model parameters and model stability margins [55]. This might indicate the higher versatility of IPMs, but it also increases considerably their indeterminacy and decreases their robustness, particularly due to the high inter-and intrasubject variability of their input parameters.…”
Section: Inverted-pendulum Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The behaviour of IPMs is harder to analyse and, therefore, less practical for day-to-day design practice. While a linear SDOF MSD model needs only three parameters ( , , and ) to be defined, similar IPMs need a minimum of six independent parameters such as body mass, angle of attack, length of leg at rest, leg stiffness, leg damping ratio, and initial system energy and, in the case of more complex models, feet model parameters and model stability margins [55]. This might indicate the higher versatility of IPMs, but it also increases considerably their indeterminacy and decreases their robustness, particularly due to the high inter-and intrasubject variability of their input parameters.…”
Section: Inverted-pendulum Modelsmentioning
confidence: 99%
“…Qin et al [55] used a bipedal IPM to simulate the interaction of a walking pedestrian with a beam structure. The human IPM had two DOFs, and , as shown in Figure 11(b).…”
Section: Inverted-pendulum Modelsmentioning
confidence: 99%
“…Full-scale dynamic measurements on service structures has shown that humans can change structural vertical dynamic properties [1,2], which has also been confirmed by a measurement experiment on a beam bearing different numbers of persons in Shahabpoor et al [3]. To explain the vibration mechanism induced by humans, some human-structure models have been proposed, including a one-person model [4,5] and a crowd model [6][7][8][9]. Zhou et al [6,7] studied vertical dynamic characteristics of structure under a modeled human oscillator.…”
Section: Introductionmentioning
confidence: 80%
“…Alonso et al [10] also recommended a vertical crowd-structure interaction model to analyze the effect of modal properties variations of a footbridge. To consider gait details, a human-structure interaction with bipedal pedestrian model was proposed by Qin et al [4,5]. Gao and Yang [11][12][13] extended this model to a crowd-structure interaction, based on a stability improvement technique.…”
Section: Introductionmentioning
confidence: 99%
“…Zivanovic (2015) reviewed the experimental and numerical developments of lightweight structures under human actions. Qin et al (2013 and2014) studied dynamic performances of footbridge under a walking biomechanical bipedal pedestrian model based on a constant walking energy level. However, the vertical vibrational stability of structure under dynamic crowds is none.…”
Section: Introductionmentioning
confidence: 99%